89=d+13⋅7

Rewrite the equation as d+13⋅7=89.

d+13⋅7=89

Combine 13 and 7.

d+73=89

Subtract 73 from both sides of the equation.

d=89-73

To write -73 as a fraction with a common denominator, multiply by 33.

d=89-73⋅33

Write each expression with a common denominator of 9, by multiplying each by an appropriate factor of 1.

Multiply 73 and 33.

d=89-7⋅33⋅3

Multiply 3 by 3.

d=89-7⋅39

d=89-7⋅39

Combine the numerators over the common denominator.

d=8-7⋅39

Simplify the numerator.

Multiply -7 by 3.

d=8-219

Subtract 21 from 8.

d=-139

d=-139

Move the negative in front of the fraction.

d=-139

d=-139

The result can be shown in multiple forms.

Exact Form:

d=-139

Decimal Form:

d=-1.4‾

Mixed Number Form:

d=-149

Solve for d 8/9=d+1/3*7